174k views
5 votes
S implify 6p3 x P² = 3p4










1 Answer

4 votes

Answer:


p_(1) = 0 \: . \: \: p_(2) = (1)/(2)

Explanation:


6 {p}^(3) * {p}^(2) = {3p}^(4) \\ {6p}^(3 + 2) = {6p}^(5) = {6p}^(5) = {3p}^(4) \\ {6p}^(5) / 3 = 3 {p}^(4) / 3 \\ 2 {p}^(5) - {p}^(4) = {p}^(4) - {p}^(4) \\ {2p}^(5) - {p}^(4) = 0 \\ {p}^(4) (2p - 1) = 0 \\ {p}^(4) = 0 \\ 2p - 1 = 0 \\


\boxed{\bold{Answer:{\boxed{\green{\bold{p_(1) = 0 \: . \: \: p_(2) = (1)/(2)}}}}}}

┈➤ . . ⇢ ˗ˏˋ⌦ ..♡ˎˊ˗ ꒰✈꒱

╭─────────

┊╭─────────

┊✿꒷꒦ ☆○●□■

╰─────────

★ . ꜝꜞ ᳝ ࣪ hope that helped! ʬʬ

User Dick McManus
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.